Gagasan Cobb, Polya Dan Zahorik Tentang Belajar Matematika - Fatiya, Ifti; Apriliana, Reynata Tri Putri; Kusno, Kusno; Akhsani, Lukmanul (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
The integration of Cobb's social constructivism, Polya's problem-solving strategy, and Zahorik's contextual learning is a mathematics learning approach that emphasizes student activity, social interaction, and the connection between abstract concepts and real-life experiences. Through discussion, group work, and negotiation of meaning, students collaboratively build mathematical understanding so that they not only memorize procedures but also understand the reasoning behind problem solving. Polya's stages help students think systematically in understanding problems, planning strategies, implementing solutions, and reviewing results, which trains reflective and critical thinking skills. Contextual learning makes mathematics more meaningful and relevant to everyday life, increases motivation to learn, and facilitates the transfer of knowledge to new situations. This integrated approach has the potential to develop problem-solving and higher-level mathematical thinking skills, while creating a collaborative and supportive classroom atmosphere, which requires teachers to be adaptive, reflective, and flexible in their application of the curriculum.